Removal of Crystal Violet Dye from Aqueous Solutions through Adsorption onto Activated Carbon Fabrics - Mulla, Batuhan; Ioannou, Kyriacos; Kotanidis, Gkerman; Ioannidis, Ioannis; Constantinides, Georgios; Baker, Mark A.; Hinder, Steven J.; Mitterer, Christian; Pashalidis, Ioannis; Kostoglou, Nikolaos; Rebholz, Claus (My University, 2024)
The removal of contaminants from aqueous solutions by adsorption onto carbonaceous materials has attracted increasing interest in recent years. In this study, pristine and oxidized activated carbon (AC) fabrics with different surface textures and porosity characteristics were used for the removal of crystal violet (CV) dye from aqueous solutions. Batch adsorption experiments were performed to investigate the CV adsorption performance of the AC fabrics in terms of contact time, temperature, adsorbate concentration and adsorbent amount. Evaluation of the thermodynamic parameters and the adsorption performance of the AC fabrics in ground water and sea water solutions were also carried out. Langmuir isotherm model, pseudo first and pseudo second order kinetics models were utilized to analyze and fit the adsorption data. The introduction of oxygen-based functional groups on the surface of AC fabrics was carried out through a nitric acid treatment. This oxidation process resulted in a significant reduction in the surface area and pore volume, along with a small increase in the average pore size and a significant enhancement in the CV adsorption capacity, indicating that the dye molecules are mainly adsorbed on the external surface of the carbon fabrics. The herein evaluated 428 mg/g adsorption capacity at 55 °C for the oxidized non-woven AC fabric is one of the highest adsorption capacity values reported in the literature for CV removal using AC materials. Thermodynamic studies showed that the adsorption occurs spontaneously and is an endothermic and entropy-driven reaction. Furthermore, pristine and oxidized non-woven AC fabrics displayed more than 90% CV uptake from sea water samples, underlining the great potential these fabrics possess for the removal of dyes from natural/multicomponent waters.
Keywords: activated carbon fabrics; crystal violet removal; microscopic characterization; spectroscopic characterization; thermodynamics; water treatment